CONTEMPORARY ISSUES OF SURGICAL TREATMENT OF BILIARY AND PANCREATICODUODENAL ORGANS DISEASES - A. Yu. BARANNIKOV; V. D. SAKHNO (Кубанский научный медицинский вестник)
Aim. To analyze the literary sources on the surgical treatment of diseases of the periampullary organs and highlight the contemporary and unresolved problems.Conclusion. At the current stage of medical development, it was possible to reduce mortality after pancreaticoduodenal resection of less than 5%, but the incidence of complications reaches 30-70% and does not tend to decrease. The most formidable complications are the failure of pancreaticodigestive anastomosis and pancreatic necrosis of the stump of the pancreas, the main prognostic risk factor for which is the "soft" parenchyma of the organ. The "softness" of the parenchyma, as a rule, is evaluated intraoperatively by visual examination and palpation. At present, the literature does not report research on the objective and pre-operative evaluation of this criterion. In order to prevent complications, a huge variety of technical solutions for the treatment of the distal stump of the pancreas have been proposed, but none of them can be considered unified.